PALESTINE-ISRAEL CONFLICT: RATIONALISM VS REALISM 1988-2017 - Aljamal, Yousef M.; Ladjal, Tarek; Mohd Nor, Mohd Roslan (Journal of Al-Tamaddun, 2018)
Realist and Rationalist approaches have been adopted from 1988-2013 in the Palestinian/Israeli conflict in the context of power and interest. The one-state solution, proposed in 1944 and 1964 by the Communist Party and the PLO, a rational proposal by then, was rejected by realists. In 1988, the two-state solution was brought to the international arena by the late PLO Chairman Yasser Arafat. His proposal was considered a compromise by traditional realists. In Israel, this proposal didn’t receive much attention, yet in 1993, it became the basics of negotiations with Palestinians. At that time, realists, both in Palestine and Israel refused it. The failure of two-state solution encouraged the rise of one-state solution again when the Palestinian Civil Society in 2005 called for a comprehensive BDS campaign to bring Israel accountable and establish one democratic state for both peoples. The proposal was rejected by the realists who proposed two-state solution, and realists who rejected the idea of two states for two peoples, yet the increasing number of people supporting one-state solution bodes for a promising future for it.